Spathius Nees, 1818 (Hymenoptera: Braconidae, Doryctinae) from China with a key to species - Tang, Pu; Belokobylskij, Sergey; Chen, Xue-Xin (Zootaxa, 2015)
One hundred and twenty-nine Chinese species of Spathius Nees, 1819 are recognized, of which thirty-five species are described as new to science: S. aciculatus sp. nov., S. albithorax sp. nov., S. angustalatus sp. nov., S. aspratiloides sp. nov., S. basalis sp. nov., S. beatoides sp. nov., S. cephalus sp. nov., S. clavator sp. nov., S. daweiensis sp. nov., S. ferrugineus sp. nov., S. flavicorpus sp. nov., S. gutianensis sp. nov., S. hainanicola sp. nov., S. longulator sp. nov., S. macrurus sp. nov., S. moscoides sp. nov., S. nehebrus sp. nov., S. neleiformis sp. nov., S. parallelus sp. nov., S. parimbecillus sp. nov., S. proximoscus sp. nov., S. pseudaphareus sp. nov., S. pseudido sp. nov., S. pseudocritolaus sp. nov., S. quasiasander sp. nov., S. rectangulus sp. nov., S. rugosivertex sp. nov., S. spinosus sp. nov., S. striolatiformis sp. nov., S. subcyparissus sp. nov., S. suberymanthus sp. nov., S. tanae sp. nov., S. virgulatus sp. nov., S. wuae sp. nov., and S. xui sp. nov. Twenty-eight species are recorded from China for the first time: S. amoenus Belokobylskij, 1998; S. capys Nixon, 1943; S. cavus Belokobylskij, 1998; S. cyparissus Nixon, 1943; S. depressithorax Belokobylskij, 1998; S. fasciatus Walker, 1874; S. femoralis (Westwood, 1882); S. galinae Belokobylskij et Strazanac, 2012; S. habui Belokobylskij et Maeto, 2009; S. hephaestus Nixon, 1943; S. hikoensis Belokobylskij, 1998; S. ibarakius Belokobylskij et Maeto, 2009; S. ishigakus Belokobylskij 2009; S. konishii Belokobylskij, 2009; S. kunashiri Belokobylskij, 1998; S. leschii Belokobylskij, 1998; S. longipetiolus Belokobylskij et Maeto, 2009; S. melpomene Nixon, 1943; S. nixoni Belokobylskij et Maeto, 2009; S. paramoenus Belokobylskij et Maeto, 2009; S. parochus Belokobylskij et Maeto, 2009; S. piperis Wilkinson, 1931; S. planus Belokobylskij, 1998; S. pseudaspersus Belokobylskij, 2009; S. pumilio Belokobylskij, 2009; S. rubidus (Rossi, 1794); S. testaceitarsis (Cameron, 1908), and S. vladimiri Belokobylskij, 1998. The following new synonyms are proposed: S. crebristriatus Chao, 1978 and S. mundus Chao, 1978 with S. araeceri Nixon, 1943; S. tanycoleosus Shi et Chen, 2004 with S. exarator Chao, 1978; S. fukienensis Chao, 1957 with S. japonicus Watanabe, 1937; S. changbaishanensis Chen et Shi, 2004 with S. oriens Belokobylskij, 1998 (stat. nov.); S. applanatus Chen et Shi, 2004 with S. phymatodis Fischer, 1966; S. bellus Chao, 1957 and S. agrili Yang, 2005 with S. sinicus Chao, 1957; S. lunganjiding Chao, 1977 and S. shennongensis Chen et Shi, 2004 with S. verustus Chao, 1977. The records of S. brevicaudis Ratzeburg, S. esakii Watanabe, S. ruficeps (Smith) and S. labdacus Nixon in China are considered as invalid.